Acyl-CoA-binding protein (ACBP): the elusive ‘hunger factor' linking autophagy to food intake - Pedro, José Manuel Bravo-San (Cell Stress, 2019)
The best-known appetite-regulating factors identified in rodents are leptin, an appetite inhibitor, and ghrelin, an appetite stimulator. Rare cases of loss-of-functions mutations affecting leptin and its receptor, as well as polymorphisms concerning ghrelin and its receptor, have been documented in human obesity, apparently validating the relevance of leptin and ghrelin for human physiology. Paradoxically, however, the overwhelming majority of obese individuals manifest high leptin and low ghrelin plasma levels, suggesting that both factors are not directly disease-relevant. We recently discovered that acyl-CoA-binding protein (ACBP), also known as diazepam-binding inhibitor (DBI), acts as an efficient lipogenic and appetite stimulator in mice. Indeed, in response to starvation, ACBP/DBI is released from tissues in an autophagy-dependent fashion and increases in the plasma. Intravenous injection of ACBP/DBI stimulates feeding behavior through a reduction of circulating glucose levels, and consequent activation of orexigenic neurons in the hypothalamus. In contrast, neutralization of ACBP/DBI abolishes the hyperphagia observed after starvation of mice. Of note, ACBP/DBI is increased in the plasma of obese persons and mice, pointing to a convergence (rather than divergence) between its role in appetite stimulation and human obesity. Based on our results, we postulate a novel ‘hunger reflex' in which starvation induces a surge in extracellular ACBP/DBI, which in turn stimulates feeding behavior. Thus, ACBP/DBI might be the elusive ‘hunger factor' that explains increased food uptake in obesity.